Applying High-Resolution Impedance Manometry for Detecting Swallowing Change in Anterior Cervical Spine Surgery Patients - Lai, Chih-Jun; Cheng, Ya-Jung; Lai, Dar-Ming; Wu, Chun-Yu; Chang, Wen-Ting; Tsuang, Fon-Yih (Frontiers in Surgery, 2022)
Background: Objectively detecting perioperative swallowing changes is essential for differentiating the reporting of subjective trouble sensations in patients undergoing anterior cervical spine surgery (ACSS). Swallowing indicates the transmission of fluid boluses from the pharynx (velopharynx, oropharynx, and hypopharynx) through the upper esophageal sphincter (UES). Abnormal swallowing can reveal fluid accumulation at the pharynx, which increased the aspiration risk. However, objective evidence is limited. High-resolution impedance manometry (HRIM) was applied for an objective swallowing evaluation for a more detailed analysis. We aimed to elucidate whether HRIM can be used to detect perioperative swallowing changes in patients undergoing ACSS. Methods: Fourteen patients undergoing elective ACSS underwent HRIM with the Dysphagia Short Questionnaire (DSQ, score: 0-18) preoperatively (PreOP), on postoperative at day one (POD1), and postoperative at day seven (POD7). We calculated hypopharyngeal and UES variables, including hypopharyngeal mean peak pressure (PeakP) and UES peak pressure, representing their contractility (normal range of PeakP, 69-280 mmHg; peak pressure, 149-548 mmHg). The velopharynx-to-tongue base contractile (VTI) was also calculated (normal range, 300-700 mmHg.s.cm), indicating contractility. The swallowing risk index (SRI) from HRIM combined with four hypopharyngeal parameters, including PeakP, represents the global swallowing function (normal range, 0-11). A higher SRI value indicated higher aspiration. Results: SRI was significantly higher on POD1 (10.88 ± 5.69) than PreOP (6.06 ± 3.71) and POD7 (8.99 ± 4.64). In all patients, PeakP was significantly lower on POD1 (61.8 ± 18.0 mmHg) than PreOP (84.9 ±34.7 mmHg) and on POD7 (75.3 ± 23.4 mmHg). The UES peak pressure was significantly lower on POD1 (80.4 ± 30.0 mmHg) than PreOP (112.9 ± 49.3 mmHg) and on POD7 (105.6 ± 59.1 mmHg). Other variables, including VTI, did not change significantly among the three time points. DSQ scores were 1.36, 3.43, and 2.36 at PreOP, POD1, and POD7 respectively. Conclusions: With similar trends in DSQ and SRI, swallowing was significantly decreased on POD1 because of decreased hypopharyngeal and UES contractility but recovered to the preoperative state on POD7 after ACSS. Applying HRIM is superior to DSQ in detecting mechanisms and monitoring the recovery from swallowing dysfunction.